2013
DOI: 10.1017/s0021859613000749
|View full text |Cite
|
Sign up to set email alerts
|

Production and carcass traits of purebred Nordic Red and Nordic Red×beef breed crossbred bulls

Abstract: SUMMARYThe objective of the current study is to determine the beef production traits of purebred Nordic Red (NR) and NR×beef breed crossbred bulls. The data collected from slaughterhouses included observations of 164 812 purebred NR, 2329 NR×Aberdeen Angus, 1466 NR×Blonde d'Aquitaine, 1044 NR×Charolais, 782 NR×Hereford, 5293 NR×Limousin and 1270 NR×Simmental bulls. For estimating valuable cuttings, a separate dataset including a total of 16 827 observations was collected. Crossbreeding NR cows with late-maturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
1
5
1
1
Order By: Relevance
“…At the start (3.3-3.8 months old), the liveweight of the C steers was 25 kg higher than for D steers, and at slaughter this breed difference had increased to 42 kg across the two feed intensities. This result was a surprisingly low increase in difference compared to that in previous studies [14][15][16]37]. However, those studies generally used higher feed intensities, even compared with the production system with a moderately high feed intensity (H) strategy in the present study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…At the start (3.3-3.8 months old), the liveweight of the C steers was 25 kg higher than for D steers, and at slaughter this breed difference had increased to 42 kg across the two feed intensities. This result was a surprisingly low increase in difference compared to that in previous studies [14][15][16]37]. However, those studies generally used higher feed intensities, even compared with the production system with a moderately high feed intensity (H) strategy in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…The superiority of dairy × beef crossbreeds compared to pure-bred dairy cattle has been established in previous studies, but mainly in intensive rearing conditions [14][15][16]. Eriksson et al [17] show that the breed effect of using beef breed sires for dairy cows is greater in intensive than extensive production systems, as the genetic potential of the beef breed can be utilized in the former.…”
Section: Introductionmentioning
confidence: 99%
“…The one possible way by which carcass weight can increase without a subsequent increase in fatness is to inseminate dairy cows with semen derived from beef cattle if the calves are not to be used as replacement animals on the dairy farm. For example, Huuskonen et al (2013Huuskonen et al ( , 2014 concluded that crossbreeding with Continental beef breeds (Ba, Ch, Li, Si) had favourable effects both on daily carcass gain and carcass quality traits of the progeny when compared with purebred dairy bulls.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality beef that meets consumer expectations can only be produced in beef and crossbred cattle herds characterised by high productivity (Sakowski et al 2001). When dairy cattle production predominates, the quantity and quality of beef can be effectively increased through commercial crossing of beef bulls with dairy cows and creating herds for the purpose of beef production (Huuskonen et al 2014). The offspring produced by commercial crossing are characterised by higher fattening performance and higher slaughter quality (Nogalski and Kijak 2001).…”
Section: Introductionmentioning
confidence: 99%